Ontogeny and tissue differentiation of the pelvic girdle and hind limbs of anurans - Manzano, Adriana Silvina (2013)
We present the ontogeny of the integrated musculoskeletal complex that comprises the pelvic girdle and hind limbs of anurans. Our histological data show that the pelvic girdle originates from a single mesenchymatic condensation. The tissue differentiation sequence is cartilage, muscle and tendon. The intrusion of the ischiadic nerve into the limb bud is produced very early in ontogeny. The pre-cartilage appears in the pre-motile stage. Therefore, the nerve produces a movement analogous to the ?embryonic motility? that would induce the emergence of the pre-cartilage. The acetabulum is the first of all cavitation processes to form, the second one being the knee. The acetabulum appears before the muscles are mature, although it has been stressed that the muscle contraction maintains joint progenitors committed to their fate. Our data indicate an explosive differentiation of all 11 muscular masses together. We provide three new characters that support the monophyly of Hyloides, Acosmanura and Neobatrachia.